2023
DOI: 10.3390/cancers15030743
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Radiomics in Microvascular Invasion Risk Stratification and Prognostic Assessment in Hepatocellular Carcinoma: A Meta-Analysis

Abstract: Background: Primary liver cancer is the sixth most commonly diagnosed cancer and the third leading cause of cancer death. Advances in phenomenal imaging are paving the way for application in diagnosis and research. The poor prognosis of advanced HCC warrants a personalized approach. The objective was to assess the value of imaging phenomics for risk stratification and prognostication of HCC. Methods: We performed a meta-analysis of manuscripts published to January 2023 on MEDLINE addressing the value of imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Preoperative prediction of MVI in patients with HCC is of great significance for clinical treatment decisions. Recently, many studies have confirmed that radiomics could be an accurate and effective tool for MVI prediction in HCC patients [ 21 , 22 ], which holds promise for the non-invasive prediction and personalized treatment. However, previous radiomics studies have only focused on static radiomics and have ignored the change pattern of the static features over time.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative prediction of MVI in patients with HCC is of great significance for clinical treatment decisions. Recently, many studies have confirmed that radiomics could be an accurate and effective tool for MVI prediction in HCC patients [ 21 , 22 ], which holds promise for the non-invasive prediction and personalized treatment. However, previous radiomics studies have only focused on static radiomics and have ignored the change pattern of the static features over time.…”
Section: Discussionmentioning
confidence: 99%
“…55 Radiogenomics in hepatocellular carcinoma has shown promise in identifying gene patterns related to aggressive imaging features and in predicting microscopic vascular invasion on pathology. 56 In lung cancer, lung ablation and radiogenomics has correlated imaging characteristics with mutation status, aiding in predicting treatment response. 57,58 KRAS mutation status 57 in colorectal cancer has been linked to outcomes after radio-embolization, guiding the need for larger ablation margins.…”
Section: Role Of Genomics In Treatment Planning and Prognosismentioning
confidence: 99%